IgG Antibody Titers Against Ascaris lumbricoides, Strongyloides stercolaris, and Toxocara canis in Venezuelan Patients with Asthma or COPD - De Sanctis, Juan Bautista; Moreno, Dolores; Larocca, Nancy; Garmendia, Jenny Valentina (Tropical medicine and infectious disease, 2024)
It has been suggested that parasitic infections, common in Latin American populations, may amplify the inflammatory response of the airways. There are several reports of atopic and asthmatic patients but few reports of parasitic infection in COPD patients. This study aimed to determine the prevalence of parasitic infections in COPD patients compared with atopic and asthmatic patients attending the Institute of Immunology outpatient clinics and the pneumology service of the University hospital. A case-control study was conducted compising 100 patients with bronchial asthma, 100 patients with COPD, 100 individuals with atopy without respiratory symptoms, and 100 healthy individuals. Serum-specific IgG antibodies against the parasites Ascaris lumbricoides (Al), Strongyloides stercolaris (Ss), and Toxocara canis (Tc) were measured by ELISA. IgE levels were used as an indirect indicator of atopy. Positive IgG for Al was observed in all groups, predominantly in the atopic cohort; Ss positiveness was recorded only in four COPD patients, and Tc positiveness was observed in all groups except in controls. Significant correlations exist between the values of Al and IgE in controls, atopic, and asthmatic patients without COPD. No correlation was found for Tc. IgE levels and the forced expiratory volume in 1 s (FEV1) correlate only in atopic and asthmatic patients. Parasitic infections are common in atopic patients and moderate and severe asthmatic and COPD patients. Anti-inflammatory treatment may be responsible for the increased frequency of infection in moderate and severe asthmatic and COPD patients.
Keywords: IgE; eosinophils; Ascaris lumbricoides; Toxocara canis; Strongyloides stercolaris; Giardia lamblia; atopy; asthma; COPD